Perfil de resistência a antibióticos e a terapia fotodinâmica antimicrobiana exibida por isolados ambientais, orais e extra-orais de Serratia marcescens - Parente, Ticiana Mont'Alverne Lopes (2010)
Serratia marcescens is widely distributed in nature, but has emerged in the last years as important nosocomial pathogen with resistance of many antimicrobial drugs. This study aimed to verify the susceptibility of Serratia marcescens isolates from environment, from oral infections and from extra-oral infections to different antibiotics and evaluate the antimicrobial effect of photodynamic antimicrobial therapy as biotechnology tools reducing bacterial growth in planktonic cells and biofilm. E-test® were performed for fifty-five strains and the PACT for the thirty strains more resistant to antimicrobials tested. The antimicrobial effect of toluidine blue O, associated with 4,72 J cm-2 of a light-emitting diode , was evaluated. Before and after the treatments, bacterial inocula were analysed with regard to the number of colony- forming units. For antimicrobials, we observed that the 55 strains analyzed, 13 (23.63%) were resistant to doxycycline, but only one (1.81%) isolate showed resistance to ciprofloxacin, another to tobramycin and another to cefotaxime, 24 ( 43.63%) strains had intermediate sensitivity to doxycycline, all were sensitive to imipenem and most were sensitive to ciprofloxacin, tobramycin and cefotaxime Statistical analysis showed no significant differences in resistance of samples of different origins for drugs DX, CT, and IP. Considering the resistance to CI, the environmental samples were significantly more resistant than samples oral and extra-oral. For the drug TM, the oral samples were significantly more sensitive than the other samples. The irradiation of planktonic and biofilm cultures in the absence of TBO (L+S-), incubation with TBO alone (L-S+) and untreated control group (L-S-) had no significant effect on the viability of strains of S. marcescens studied (p <0.05). Significant decreases in bacterial viability was observed only when planktonic and biofilm culture of environmental strains, oral and extra-oral S. marcescens were exposed to toluidine blue O and LED light at the same time (L+S+). Significant reductions in bacterial counts were observed by antimicrobial photodynamic therapy ranging from 10-11 to 10-7.The association of TBO and light, with energy density 4,72 J cm-2, was effective in reducing the viability of bacterial strains in environmental, oral and extra-oral S. marcescens and can be a useful biotechnological tool in the control of bacterial resistance.